Effect of styrene maleic acid WIN55, 212-2 micelles on neuropathic pain in a rat model. (May 2015) - Linsell, Oliver; Brownjohn, Philip W.; Nehoff, Hayley; Greish, Khaled; Ashton, John C.
Abstract Cannabinoid receptor agonists are moderately effective at reducing neuropathic pain but are limited by psychoactivity. We developed a styrene maleic acid (SMA) based on the cannabinoid WIN 55, 212-2 (WIN) and tested in a rat model of neuropathic pain and in the rotarod test. We hypothesized that miceller preparation can ensure prolonged plasma half-life being above the renal threshold of excretion. Furthermore, SMA-WIN could potentially reduce the central nervous system effects of encapsulated WIN by limiting its transport across the blood–brain barrier. Using the chronic constriction injury model of sciatic neuropathy, the SMA-WIN micelles were efficacious in the treatment of neuropathic pain for a prolonged period compared to control (base WIN). Attenuation of chronic constriction injury-induced mechanical allodynia occurred for up to 8 h at a dose of 11.5 mg/kg of SMA-WIN micelles. To evaluate central effects on motor function, the rotarod assessment was utilized. Results showed initial impairment caused by SMA-WIN micelles to be identical to WIN control for up to 1.5 h. Despite this, the SMA-WIN micelle formulation was able to produce prolonged analgesia over a time when there was decreased impairment in the rotarod test compared with base WIN.